Does early compared to late fortification of human milk for preterm infants improve clinical outcomes?. (3rd July 2019) - Godden, Beth; Collins, Carmel T; Hilditch, Cathie; McLeod, Gemma; Keir, Amy
Abstract : Aim: This evidence‐based review aims to answer the following structured clinical question: In preterm infants <37 weeks' gestation (patient), does early fortification of breast milk (intervention) compared to late fortification (control) improve growth outcomes at the time of discharge or affect length of hospital stay (outcome)? Methods: MEDLINE, Embase, Maternity and Infant Care Database and Evidence‐Based Medicine Reviews were searched for articles published from 2000 onwards that were relevant to the structured clinical question. The National Institute for Health and Care Excellence, National Health and Medical Research Council, Agency for Healthcare Research and Quality, National Institute of Health and Turning Research into Practice databases were also searched, and reference lists of relevant articles were reviewed. Results: A total of 167 articles, after removal of duplicates, were found and screened by title and abstract. Five full‐text articles were ultimately included in the review. Conclusions: The results of this review suggest that early fortification is safe and well tolerated. However, earlier fortification has not been shown to have a significant impact on growth outcomes at time of discharge or length of stay. More research is required to determine if early fortification of breast milk may have benefits regarding longer‐term growth and neurodevelopmental outcomes.